2010
DOI: 10.1210/jc.2010-0512
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Psychopathology and Maladaptive Personality Traits after Long-Term Cure of Cushing’s Disease

Abstract: Patients with long-term cured CD show an increased prevalence of psychopathology and maladaptive personality traits. These observations suggest irreversible effects of previous glucocorticoid excess on the central nervous system rather than an effect of pituitary tumors and/or their treatment in general. This may also be of relevance for patients treated with high doses of exogenous glucocorticoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(70 citation statements)
references
References 29 publications
7
61
1
1
Order By: Relevance
“…Patients with Cushing's disease showed also the highest rates of depression compared with other patient groups. So far, psychiatric aspects of Cushing's disease have been the best described in the recent literature (17,18,19,20). However, the higher incidence of depression for patients with Cushing's disease in our study is partly explained by the fact that there are predominantly females in this group.…”
Section: Clinical Study S M Leistner and Others Qol In Patients With contrasting
confidence: 56%
See 1 more Smart Citation
“…Patients with Cushing's disease showed also the highest rates of depression compared with other patient groups. So far, psychiatric aspects of Cushing's disease have been the best described in the recent literature (17,18,19,20). However, the higher incidence of depression for patients with Cushing's disease in our study is partly explained by the fact that there are predominantly females in this group.…”
Section: Clinical Study S M Leistner and Others Qol In Patients With contrasting
confidence: 56%
“…Sievers et al (15) and Tiemensma et al (16) showed that acromegaly is associated with an increased prevalence and a specific pattern of affective disorders. Also for Cushing's disease, many studies have stressed that depression and anxiety-related personality disorders are common comorbidities in these patients (17,18,19,20,21). Patients with prolactinomas seem to experience increased neuroticism, high fear of uncertainty, and also increased fatigability and asthenia (22), but further studies are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This has already been observed in multiple other medical conditions (24). This relationship is a relevant observation, since patients with longterm cure of CS have persistent complaints reflected in impaired QoL (3)(4)(5). These complaints are often misunderstood and difficult to treat.…”
Section: Discussionmentioning
confidence: 74%
“…Following successful treatment of hypercortisolism, signs and symptoms improve substantially. However, prolonged, excessive exposure to glucocorticoids may have long-lasting adverse effects on behavioral and cognitive functions, due to functional and structural alterations in specific brain target areas (1)(2)(3)(4). Furthermore, these patients do not completely return to their premorbid level of functioning, and quality of life (QoL) is persistently impaired despite long-term cure of CS (5).…”
Section: Introductionmentioning
confidence: 99%
“…A higher prevalence of 'maladaptive' personality traits in CS patients even after long-term cure may affect their everyday QoL (69). They appear to perceive that they are characterized by 'unpleasant' increased anxiety traits (pessimism, neuroticism, shyness with strangers and low extraversion), and try to answer in a rather 'pleasant' (or socially desirable) way.…”
Section: Cushing's Diseasementioning
confidence: 99%